2020
DOI: 10.3389/fenvs.2020.00133
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost Microbial Community Structure Changes Across the Pleistocene-Holocene Boundary

Abstract: Despite the presence of well-documented changes in vegetation and faunal communities at the Pleistocene-Holocene transition, it is unclear whether similar shifts occurred in soil microbes. Recent studies do not show a clear connection between soil parameters and community structure, suggesting permafrost microbiome-climate studies may be unreliable. However, the majority of the permafrost microbial ecological studies have been performed only in either Holocene-or Pleistocene-aged sediments and not on permafros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
(104 reference statements)
2
14
0
Order By: Relevance
“…cellulose, xylan, and pectin; Tóth and Borsodi, 2014). Deinococcus-Thermus was detected in the older paleosols tested and has also been found in Holoceneaged samples collected in the central Yukon (Saidi-Mehrabad et al, 2020). Additionally, Pseudonocardiaceae, capable of degrading lignocellulose and chitin (Yeager et al, 2017), was detected in all of the paleosols tested, possibly indicating the presence of complex carbon in the ancient soils.…”
Section: Major Microbial Groups Found Throughout the Holocenementioning
confidence: 77%
“…cellulose, xylan, and pectin; Tóth and Borsodi, 2014). Deinococcus-Thermus was detected in the older paleosols tested and has also been found in Holoceneaged samples collected in the central Yukon (Saidi-Mehrabad et al, 2020). Additionally, Pseudonocardiaceae, capable of degrading lignocellulose and chitin (Yeager et al, 2017), was detected in all of the paleosols tested, possibly indicating the presence of complex carbon in the ancient soils.…”
Section: Major Microbial Groups Found Throughout the Holocenementioning
confidence: 77%
“…The permafrost origin is additionally important in driving the community structure, since significant differences in community composition were reported from late Pleistocene lacustrine-alluvial and Ice Complex (Yedoma) sediments (Rivkina et al, 2016). Recently, the transition from Pleistocene to Holocene was shown to initiate a major threshold-type shift in the composition and structure of permafrost microbial community in Central Yukon (Saidi-Mehrabad et al, 2020). These results draw particular attention to the potential effect of climate change on microbial activity and trace gas production.…”
Section: Introductionmentioning
confidence: 94%
“…The studied samples from ice wedges of the Mamontova Gora exposure demonstrate significant differences in the community composition of the lower and upper Ice Complex horizons, further confirming that these are different generations of ice wedges with different origin (Figures 10,11). We assume that the observed differences are related more to the genesis than the differential preservation of DNA since the microbial community structure within an epoch is relatively stable over time (Shade et al, 2013), while once the system surpasses a threshold, microbial parameters rapidly shift to a new stable state (Saidi-Mehrabad et al, 2020).…”
Section: Ice Complexes: Ice Wedgesmentioning
confidence: 99%
See 1 more Smart Citation
“…Permafrost thaw leads to rapid changes in microbial community composition and function, including shifts in several metabolites and genes involving nitrogen and carbon cycling in response to permafrost thaw, and during a thaw event, community function within permafrost quickly converges to that of the active layer ( Mackelprang et al, 2011 ; Coolen and Orsi, 2015 ; Monteux et al, 2018 ; Johnston et al, 2019 ; Messan et al, 2020 ; Saidi-Mehrabad et al, 2020 ). Consistent with the pattern of permafrost thaw affecting soil microbial communities, Inglese et al (2017) found that active layer detachments, a form of permafrost disturbance, significantly affect fungal and Archaeal community composition of the active layer.…”
Section: Introductionmentioning
confidence: 99%